The Development of Cosmetology Related Departments of Five-Year Junior Colleges at Technological and Junior Colleges in Taiwan - YEH, Ju-Hsuan; Tsai-Yun, Lo; Hsiang-Ping, Chou (Advances in Social Sciences Research Journal, 2018)
The purpose of this study is to investigate the development of cosmetology related departments of five-year junior colleges at technological and junior colleges. Literature review was used to analyze the development of cosmetology related departments, college features, curriculum, and the changes on enrollments over the years, and further explore the development process of cosmetology related departments of five-year junior colleges and the relations to related industries.